PEMERIKSAAN SENSORIMOTOR DENGAN METODE PANESS DAN FLETCHER BERDASARKAN JENIS KELAMIN DAN UMUR PADA ANAK UMUR 712 TAHUN DI SDN SEJAHTERA IV KOTAMADYA BANDUNG - Ludmila , Uni Gamayani, Siti Aminah (Neurona Majalah Kedokteran Neuro Sains, 2009)
INTRODUCTION SENSORIMOTOR STAGE IS THE FIRST STAGE OF INDIVIDUALS DEVELOPMENT COGNITIVE FUNCTION SENSORIMOTOR EXAMINATION IS DONE TO DETECT BRAIN DYSFUNCTION FOCAL LATERALIZED OR DIFFUSE THE AIM OF THE STUDY IS TO COLLECT PRIMARY DATA AND TO FIND OUT THE DIFFERENCE OF SENSORIMOTORS EXAMINATION RESULTS BASED ON GENDER AND AGE FROM CHILDREN AGED 7 TO 12 YEARS